Understanding Physical Literacy of Physical Education Teachers - Apriliyanto, Rizki; Sulaiman, Ahmad (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
The purpose of this study is to ascertain how well physical education teachers comprehend physical literacy. The "perceived physical literacy instrument" (PPLI), which has nine items and a validity level of 0.82, is used to test one's comprehension of physical literacy (very good). Purposive sampling is a strategy used to obtain data. A questionnaire based on the PPLI instrument was distributed to 53 physical education instructors in the Jember area in order to gather knowledge data on physical literacy. Overall survey findings revealed that out of 187 questions, (18.86%) of respondents Sangat Setuju d, (42.7%) of respondents Setuju d there were 204 questions, and (18.86%) of respondents indicated they were unsure about the answers to 90 questions. The results indicate that some teachers have a limited grasp of the idea of physical literacy. This explains why physical education lessons must help teachers better comprehend and cultivate physical literacy. Even if physical education instructors' degree of understanding of physical literacy is known, other measurements must be taken to determine the total competency in physical literacy, such as physical competence, motivation, and self-confidence. Given that there are four areas of physical literacy that might be explored or investigated in the future.